Sound Energy: An Electric Source of Noise Pollution Based Power Bank - Bacosa Jr, C A; Baldovino, M A P (KnE Social Sciences, 2018)
The sound energy associated with the vibration of matter an abundant source of noise pollution, wherein the least of all types of pollution which most people ignore to recycle and turn into electricity sources. The purpose of this project is to design and develop a device that can make useful energy from noise known as noise pollution based power bank with suitable architectural design, component design, code generation, and integration system..The researcher chooses design science research methods and V Model procedure to make sure of the efficiency of the device. Noise Pollution Based Power Bank was tested in different noisy areas. The device had been tested in various places to prove capability to work in a variety of noisy environment. The efficiency of the device in terms of charging the power bank utilizing noise is proven effective especially in loud/ noisy places that make the power bank charged the battery continuously. Comparing to commercial power banks, noise pollution based power bank produced a parallel result. Charging is also performed with different gadgets that are most likely use power bank and found effective and efficient. With the future modification of the noise pollution based power bank, it is possible to make this device a basis of imminent technologies that will make a way of recycling noise pollution to be a secondary source of establishing a wide scale electricity source. Keywords: Noise Pollution, Acoustic Energy, Sound Energy, Power Bank, Alternative Energy Source, Electric Source